Pemberdayaan Masyarakat Tentang Pembuatan Pupuk Organik Dari Kotoran Ternak Di Kelurahan Hutuo, Kecamatan Limboto, Gorontalo - Erni Mohamad; Mangara Sihaloho; Perry Zakaria; Gevira Datungsolang; Neni Purnama Djaipano (Universitas Negeri Gorontalo, 2022)
This community service activity aims to reduce the community's dependence on chemical fertilizers which are increasingly expensive with the hope that this activity can improve the ability of people's knowledge in utilizing livestock manure which is not only left alone but must be processed so that it becomes useful as organic fertilizer for the purpose of increasing yields. harvest. The use of livestock manure which in this case is cow and goat manure as organic fertilizer is still very lacking among breeders. Almost 100% of farmers are not aware of the benefits of this animal manure as organic fertilizer because their focus is only on the livestock itself. Processing and utilizing livestock manure as organic fertilizer, so that people no longer depend on the use of chemical fertilizers. In this activity is to provide training to the community of livestock and farmer groups about making organic fertilizer from livestock manure (cows and goats). This activity is expected to train the community to be able to produce organic fertilizer that will be used by farmers, which has been a problem for farmers, namely crop failure caused by the community not being able to buy fertilizer due to the increasing price of chemical fertilizers. The method used is direct training to the group on the manufacture of organic fertilizer from animal waste using the fermentation method. The result of the implementation of the activity is that the community is very enthusiastic in participating in this activity. The community is interested in making/producing this fertilizer on their own, in addition to livestock manure, the community also intends to make this fertilizer themselves from waste or waste materials. Especially household waste based on the knowledge they have gained in this activity.